The voltage-mode first order universal filter using single voltage differencing differential input buffered amplifier with electronic controllability - Danupat Duangmalai; Peerawut Suwanjan (Institute of Advanced Engineering and Science, 2022)
In this research contribution, the electronically tunable first-order universal filter employing a single voltage differencing differential input buffered amplifier (VD-DIBA) (constructed from two commercially available integrated circuit (IC): the operational transconductance amplifier, IC number LT1228, and the differential voltage input buffer, IC number AD830), one capacitor and two resistors. The features of the designed first order universal filter are as follows. Three voltage-mode first-order functions, low-pass (LP), all-pass (AP) and high-pass (HP) responses are given. The natural frequency (????0) of the presented configuration can be electronically adjusted by setting the DC bias current. Moreover, the voltage gain of the LP and HP filters can be controllable. The phase responses of an AP configuration can be varied from 00 to −1800 and 1800 to 00. The power supply voltages were set at ±5 ????. Verification of the theoretically described performances of the introduced electronically tunable universal filter was proved by the PSpice simulation and experiment.